Association between anemia and diabetic lower extremity ulcers among US outpatients in the National Health and Nutrition Examination Survey: a retrospective cross-sectional study - Cao, Jinmin; Wang, Jingpei; Zhang, Saiqian; Gao, Guiyun (Frontiers in Endocrinology, 2024)
Purpose The aim of this study was to explore the relationship between hemoglobin levels, anemia and diabetic lower extremity ulcers in adult outpatient clinics in the United States. Methods A retrospective cross-sectional study was conducted on 1673 participants in the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2004. Three logistic regression models were developed to evaluate the relationship between anemia and diabetic lower extremity ulcers. Model 1 adjusted for demographic and socioeconomic variables (age, sex, race and ethnicity, educational level, family income, and marital status). Model 2 included additional health-related factors (BMI, cardiovascular disease, stroke, family history of diabetes, hyperlipidemia, alcohol and smoking status). Model 3 further included clinical and laboratory variables (HbA1c, CRP, total cholesterol, and serum ferritin levels). Stratified analyses were also conducted based on age, sex, HbA1c level, body mass index (BMI), and serum ferritin level. Results The study included 1673 adults aged 40 years and older, with a mean age of 64.7 ± 11.8 years, of whom 52.6% were male. The prevalence of diabetic lower extremity ulcers (DLEU) was 8.0% (136 participants). Anemia was found in 239 participants, accounting for 14% of the study group. Model 1 showed an OR of 2.02 (95% CI=1.28 3.19) for anemia, while Model 2 showed an OR of 1.8 (95% CI=1.13 2.87). In Model 3, the OR for DFU in patients with anemia was 1.79 (95% CI=1.11 2.87). Furthermore, when serum ferritin was converted to a categorical variable, there was evidence of an interaction between DLEU status and serum ferritin in increasing the prevalence of DLEU. Conclusion After adjusting for confounding variables, higher levels of anemia were proportionally associated with an increased risk of incident DLEU. These results suggest that monitoring T2DM patients during follow-up to prevent the development of DLEU may be important. However, further prospective studies are needed to provide additional evidence.